2001
DOI: 10.1093/toxsci/62.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of S-Ethyl Hexahydro-1H-azepine-1-carbothioate (Molinate) on Di-n-butyl Dichlorovinyl Phosphate (DBDCVP) Neuropathy

Abstract: Certain esterase inhibitors protect from organophosphate-induced delayed polyneuropathy (OPIDP) when given before a neuropathic organophosphate by inhibiting neuropathy target esterase (NTE). In contrast, they can exaggerate OPIDP when given afterwards and this effect (promotion) is associated with inhibition of another esterase (M200). In vitro sensitivities of hen, rat, and human NTE and M200 to the active metabolites of molinate, sulfone, and sulfoxide, were similar. NTE and M200 were irreversibly inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…However, when ''protective'' NTE inhibitors such as PMSF are dosed after a low non-neuropathic dose of a neuropathic OP (causing[40-50% NTE inhibition), its neurotoxicity is ''potentiated'' (Pope and Padilla 1990) or ''promoted'' (Lotti et al 1991), causing severe neuropathy. Although the target of ''potentiation'' by PMSF remains unknown, it is suspected to be another esterase related to peripheral nerve soluble PVases (Moretto 2000;Moretto et al 2001). However, the global interaction of PMSF with nerve tissue esterases has not been kinetically analyzed in detail, and it is necessary to identify which are the relevant sensitive esterases to PMSF as possible target(s) for promotion/potentiation of organophosphorus-induced delayed polyneuropathy (OPIDP) before isolation and molecular characterization.…”
Section: Introductionmentioning
confidence: 99%
“…However, when ''protective'' NTE inhibitors such as PMSF are dosed after a low non-neuropathic dose of a neuropathic OP (causing[40-50% NTE inhibition), its neurotoxicity is ''potentiated'' (Pope and Padilla 1990) or ''promoted'' (Lotti et al 1991), causing severe neuropathy. Although the target of ''potentiation'' by PMSF remains unknown, it is suspected to be another esterase related to peripheral nerve soluble PVases (Moretto 2000;Moretto et al 2001). However, the global interaction of PMSF with nerve tissue esterases has not been kinetically analyzed in detail, and it is necessary to identify which are the relevant sensitive esterases to PMSF as possible target(s) for promotion/potentiation of organophosphorus-induced delayed polyneuropathy (OPIDP) before isolation and molecular characterization.…”
Section: Introductionmentioning
confidence: 99%
“…We did not encounter reports of delayed polyneuropathy due to DDVP in humans, nor an experimental study involving DDVP. Moretto and his coworkers [28][29][30] examined experimental animals with a similar compound, di-n-butyl dichlorovinyl phosphate, which they define as a potent organophosphate for causing delayed polyneuropathy. Our case is probably the first reported OPIDP due to DDVP.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Veronesi and Padilla (1985) were able to show protection by PMSF against spinal cord lesions produced by mipafox in rats. Likewise, protection was conferred by the thiocarbamate, molinate, against OPIDN induced by di-n-butyl dichlorvos (DBDCV) in rats as well as in hens (Moretto et al, 2001).…”
Section: Protection (Prophylaxis) Against Opidnmentioning
confidence: 99%
“…The specific basis for potentiation or promotion of OPIDN has not been elucidated, but in view of the fact that potentiators or promoters delay recovery from nerve crush (Moretto et al, 1993), a plausible general explanation involves the notion of interference with mechanisms of repair of axonal injury (Lotti, 2002). In addition, although the first reports of potentiation/promotion indicated that the effective compounds were NTE inhibitors, subsequent work by Lotti and colleagues strongly suggested that the target for promotion/potentiation is not NTE (Lotti, 2002;Lotti and Moretto, 1993;Moretto et al, 1994Moretto et al, , 2001.…”
Section: Potentiation or Promotion Of Opidnmentioning
confidence: 99%